Influência do baço e de operações para tratamento de hipertensão porta esquistossomática na incidência de trombose das veias principais do sistema porta e em exames hematológicos e bioquímicos - Leonardo de Souza Vasconcellos (2011)
BACKGROUND: There are few studies that correlate the laboratory and thrombogenic effects with different surgical procedures for the treatment of schistosomal portal hypertension (SPH), whose physiopathology is not yet understood. OBJECTIVES: To correlate the size of the spleen with the serum levels of the preoperative haematological tests; to verify changes in the serum levels of haematological and biochemical tests in pre- and postoperative period; to correlate four different surgical techniques for treatment of SPH with the incidence of portal vein thrombosis in the late post-operative period; to verify if portal vein thrombosis can produce changes in the serum levels of haematological and biochemical tests. METHODS: 80 patients with SPH were divided in four groups: Group 1 (n = 16): submitted to oesophagogastric desvascularization and splenic artery ligation, Group 2 (n = 24): submitted to oesophagogastric desvascularization and total splenectomy, Group 3 (n = 30): submitted to oesophagogastric desvascularization and subtotal splenectomy preserving the upper pole and Group 4 (n = 10): submitted to oesophagogastric desvascularization, with splenectomy and autogenous splenic implants on the greater omentum. The size of the spleen was estimated by the preoperative ultrasound and correlated with the the serum levels of haematological tests. The results of haematological and biochemical tests were compared between groups. Late postoperative portal vein thrombosis was diagnosed using Doppler ultrasound. The patients were divided into two groups, with and without postoperative portal vein thrombosis and the results of haematological and biochemical tests compared, with p value < 0.05 being significant. RESULTS: The size of the spleen was not correlated with preoperative cytopenias. Thrombocytopenia was observed in 78 (97.5%) patients. Leukopenia occurred in 70 (87.5%) cases, eosinophilia in 34 (42.5%) and anemia in 56 (70%). The prothrombin activity was below 70% in 44 patients (55%). There was no difference in preoperative biochemical blood tests between groups. During the late postoperative follow-up, patients in Group 1 had a low levels of leukocytes, platelets and prothrombin activity, and a high level of international normalazed ratio (INR) Liver and kidney functions, as well as glucose and lipid levels, were similar between groups. The levels of erythrocytes, haemoglobin, haematocrit, total leukocyte and platelets were improved in all patients, while prothrombin time and INR seen only in groups 2 and 3. Portal vein thrombosis was diagnosed in 26 (42.6% ) patients and this result was not correlated with any specific group of surgical treatment. There was no difference in haematological and biochemical tests between groups with or without portal vein thrombosis. CONCLUSIONS: The size of the spleen was not correlated with the haematological tests; all patients had blood cells count raised; there was no difference in postoperative biochemical blood tests between groups. Portal vein thrombosis was diagnosed during the late postoperative follow-up in all groups, with no difference between them. This result did not interfere with the haematological or biochemical tests. KEYWORDS: Schistosomiasis, Portal hypertension, Portal vein thrombosis, Doppler ultrasound, Leukopenia, Thrombocytopenia, Anemia, Liver function, Kidney function, Glucose level, Lipids levels, Preoperative, Postoperative, Surgery, Oesophagogastric desvascularization, Splenic artery Ligation, Total splenectomy, Subtotal splenectomy, Autogenous splenic implants.